What and how: doing good research with young people, digital intimacies, and relationships and sex education. Issue 6 (1st November 2020) - Scott, Rachel H.; Smith, Clarissa; Formby, Eleanor; Hadley, Alison; Hallgarten, Lisa; Hoyle, Alice; Marston, Cicely; McKee, Alan; Tourountsis, Dimitrios
ABSTRACT: As part of a project funded by the Wellcome Trust, we held a one-day symposium, bringing together researchers, practitioners, and policymakers, to discuss priorities for research on relationships and sex education (RSE) in a world where young people increasingly live, experience, and augment their relationships (whether sexual or not) within digital spaces. The introduction of statutory RSE in schools in England highlights the need to focus on improving understandings of young people and digital intimacies for its own sake, and to inform the development of learning resources. We call for more research that puts young people at its centre; foregrounds inclusivity; and allows a nuanced discussion of pleasures, harms, risks, and rewards, which can be used by those working with young people and those developing policy. Generating such research is likely to be facilitated by participation, collaboration, and communication with beneficiaries, between disciplines and across sectors. Taking such an approach, academic researchers, practitioners, and policymakers agree that we need a better understanding of RSE's place in lifelong learning, which seeks to understand the needs of particular groups, is concerned with non-sexual relationships, and does not see digital intimacies as disconnected from offline everyday 'reality'.